Effect of Time of LED Lights Irradiation on Aquascape performance - Hariyadi Hariyadi; Aris Winaya; Mohammad Rofit Anggi Pratama (Universitas Tidar, 2020)
This study aims to determine the length of time the irradiation of LED lights is suitable for aquascape ornamental plant performance, fish survival and water quality in aquascape media. This research was conducted on 22 April 28 May 2019 in collaboration with Fisheries Faculty of Agriculture, Animal Husbandry, University of Muhammadiyah Malang. This research uses 2 types of low light aquascape plants, namely Cryptocorine Wenti and Hidrocotyle Leucepala. This research is an experimental study using RAL with 4 treatments P0 (control 12 hours of indirect sunlight), P1 (LED lights with a long exposure time 8 hours), P2 (LED lights with a long exposure time of 10 hours), P3 (LED lights with a long exposure time of 12 hours) repeated 3 times. The parameters observed include aquascape ornamental plants such as plant length, stem diameter, wet weight. In the observation of water quality including temperature, pH, DO, dissolved CO2, and water hardness. In aquascape ornamental fish in the form of survival rate and growth of ornamental aquascape fish. Analyzed with ANOVA and continued with the Least Significant Difference Test on parameters that obtained significant differences.The results showed that the irradiation time of 10 hours had a significant influence on the stem diameter of the plant, namely P (0.037) <0.05 and the LSD test showed that the length of time the irradiation of 10 hours of LED lights had a significant effect on the diameter of the aquascape stem. In the length and wet weight of aquascape ornamental plants did not show significantly different results. On the parameters of water quality, growth and graduation of fish life also did not show significantly different results from the treatment of the long exposure time given.